Effect of silver nitrate and putrescine on in vitro shoot organogenesis of Polygonum multiflorum - Park, Woo Tae; Kim, Yeon Bok; Sathasivam, Ramaraj; Kim, Haeng-Hoon; Park, Sang Un (Journal of Phytology, 2022)
Polygonum multiflorum is a flowering plant that belongs to the family Polygonaceae and it is commonly used for medicinal and ornamental purposes. Few studies have been studied about the regeneration of this species. Therefore, we aimed to develop a suitable protocol for regeneration and subsequent growth of shoots by comparing the silver nitrate (AgNO3) (ethylene inhibitor) and the putrescine (polyamine). Internode explants were cultured on shoot regeneration media (Murashige and Skoog (MS) media containing 2 mg L-1 of 6-benzylaminopurine). To analysis, the effect of AgNO3 and putrescine on shoot regeneration and length, different concentrations (mg L-1) of AgNO3 (0, 1, 5, 7, 10, and 20) and putrescine (0, 10, 30, 50, 100, and 200) were added to the MS media. The result showed that at highest concentration (20 mg L-1) of AgNO3 treatment decrease number of shoots (NOS) (1.4 ± 0.2 mm) and shoot length (9.7 ± 1.6 mm) was observed. Putrescine considerably increased the regeneration efficiency, NOS per explant, and shoot length in all the concentrations when compared to AgNO3 treatment. Among the different concentrations, the highest NOS (2.52 ± 0.2 mm) was obtained in cultures supplemented with 30 mg L-1 putrescine, whereas the further increase in putrescine concentration reduced shoot regeneration. The longest shoots (20.5 ± 1.7 mm) were achieved in cultures supplemented with 200 mg L-1 putrescine. The findings of this study indicate that the addition of putrescine to the media could be suitable for P. multiflorum micropropagation and plant transformation.